Formalisation of organisational structure as a subject of path dependency: an example from Central and Eastern Europe. - Sakowski, K.; Vadi, M.; Meriküll, J. (Post-Communist Economies, 2015)
This study examines the characteristics of organisational structures in Central and Eastern Europe using the example of Estonia. In particular, the formalisation level of the structures as a subject of path-dependent developments is observed. Quantitative and qualitative research methods are combined for the empirical evidence and data from three different sources are employed: the European Social Survey, the survey of Estonian managers and interviews with managers from Estonian software companies. The authors show that the communist past still affects organisational life today. The path this past created affects the organisational structures in the present in two ways: first, a kind of structural inertia can be observed, where the Soviet style of management with its high formalisation is still present today and limits employees' freedom to deal with their work. Second, an opposite trend can be revealed for the other actors in the same game, the managers, as another kind of path dependency exists – a process where the past has caused a powerful response, forcing the actors to react against the Soviet management style. We demonstrate that this path dependency can be perceived differently by different actors in an organisation and we show that the path dependency is a complex issue with many nuances within it.